One-Year Follow-Up of Cystic Fibrosis Patients Who Cannot Reach the Modulator Therapies Although Having Indications: What are Their Losses? - Uytun, S.; Polat, S. Eryilmaz; Tabakci, S. Ozkan; Cinel, G.; Emiralioglu, N.; Yalcin, E.; Dogru, D. (European Respiratory Soc Journals Ltd, 2022)
[Abstract Not Available]
International Congress of the European-Respiratory-Society (ERS) -- SEP 04-06, 2022 -- Barcelona, SPAIN